Total flavonoid content and analgesic activity of ethyl acetate fraction of Indian jujube (Ziziphus mauritiana lamk) leaves - Tenda, Priska Ernestina; Fatmawati Blegur; Lely A.V Kapitan (Indonesian Journal of Pharmacology and Therapy, 2022)
Indian jujube leaves (Ziziphus mauritiana Lamk) have various potential biological activity. Previous studies have proven that ethanol extracted from Indian jujube (Z. mauritiana Lamk) leaves had analgesic activity. This study aimed to determine the total flavonoid content and analgesic activity of the ethyl acetate fraction of Indian jujube (Z. mauritiana Lamk) leaves ethanol extract. Tested fraction was prepared by maceration using ethanol as solvent followed by fractionation using ethyl acetate. Identification of active compounds was performed using color reaction, and determination of total flavonoids by colorimetric method. Ethyl acetate fraction was further tested for its analgesic activity using the writhing method. Swiss-Webster white male mice were divided into 5 treatment groups consisting of negative control contained sodium-CMC, positive control contained sodium diclofenac, while groups 3-5 were given ethyl acetate fraction of Indian jujube (Z. mauritiana Lamk) leaves with doses of 50, 150, and 200 mg/kg BW. All interventions were administered as a single oral dose. 0.7% (w/v) acetic acid was used as a pain inducer. Analgesic activity was measured by calculating the percentage of writhing protection as a measure of the analgesic effect produced by each intervention. The data were analyzed using one-way Anova to compare analgesic activity between treatment groups. Results showed that ethyl acetate fraction of Indian jujube (Z. mauritiana Lamk) leaves at doses of 50, 150, and 200 mg/kg BW gave an effect that was not significantly different from sodium diclofenac as positive control. The ethyl acetate fraction of Indian jujube (Z. mauritiana Lamk) leaves ethanol extract contained flavonoids, saponin, and tannins with total flavonoid content of 22.41 ± 1.16% w/w. It can be concluded that the ethyl acetate fraction of Indian jujube (Z. mauritiana Lamk) leaves have analgesic activity in mice.